EFFECT OF SODIUM VALPROATE AND DOCOSAHEXAENOIC ACID ON INFLAMMATION IN RATS - Kunder, Sushil Kiran; Bairy, Laxminarayana Kurady; A, Avinash (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate the anti-inflammatory activity of sodium valproate and docosahexaenoic acid (DHA) supplementation using various experimental models in albino Wistar rats. Method: A total of 48 adult Wistar albino male rats were divided into 8 groups of 6 rats each. Group I was control (distilled water 1 ml/kg), Group II received intraperitoneal (i.p.) injection of indomethacin (10 mg/kg), Groups III-V were injected (i.p.) with sodium valproate 100, 200, and 400 mg/kg water, and Groups VI-VIII were given sodium valproate 100, 200, and 400 mg/kg plus DHA 300 mg/kg (i.p.), respectively. Anti-inflammatory activity was assessed using carrageenan induced paw edema and the cotton pellet granuloma models. Results: We found that higher doses of sodium valproate (400 mg/kg) used either alone or with a combination of DHA (300 mg/kg) showed a significant anti-inflammatory activity when compared to control in both the models of inflammation. Conclusion: Combination of sodium valproate along DHA has shown promising anti-inflammatory activity. Keywords: Anti-inflammatory drugs, Sodium valproate, Rat model.